Magnetotransport study of topological superconductor Cu0.10Bi2Se3 single crystal. (27th February 2018) - Li, M T; Fang, Y F; Zhang, J C; Yi, H M; Zhou, X J; Lin, C T
Abstract: We report a magnetotransport study of vortex-pinning in Cu0.10 Bi2 Se3 single crystal. The sample is demonstrated to be in clean limit and absent of Pauli spin-limiting effect. Interestingly, the resistivity versus magnetic field shows an anomalously pronounced increase when approaching the superconducting-normal state boundary for both B a p p ∥ a b and B a p p ∥ c configurations. We have investigated the flux-flowing behavior under various magnetic fields and temperatures, enabling us to establish its anisotropic vortex phase diagram. Our results suggest the Cu0.10 Bi2 Se3 can be served as one unique material for exploring exotic surface vortex states in topological superconductors.